Non-Invasive Assessment of Myocardial Perfusion Abnormality in Type 2 Diabetic Patients Without Symptoms of Coronary Artery Disease by SPECT-MPI - Azam, Mohammad Nurul; Sultana, Sadia; Roy, Sutanu; Salma, Umme (Bangladesh Journal of Nuclear Medicine, 2023)
Introduction: Coronary artery disease (CAD) is the most common chronic macrovascular complication of diabetes mellitus. Diabetic patients have a high incidence of silent ischemia and MI due to autonomic neuropathy. SPECT imaging is a well-established, non-invasive procedure that offers perfusion and functional information for diagnosis and risk stratification, facilitating the early detection of CAD. Objective: To detect myocardial perfusion abnormality by SPECT-MPI in type 2 diabetic patients without symptoms of CAD. Methods: A total of eighteen diabetic patients with no history of typical CAD, with or without risk factors, underwent gated SPECT-MPI using 99mTc-sestaMIBI. A single-day stress–rest protocol with adenosine was done in each patient. Result: Six out of eighteen patients (33.3%) showed abnormal scans suggestive of myocardial ischemia or infarction. Four of these patients had reversible perfusion defects, one had a fixed perfusion defect, and one had a mixed defect. Among these patients, single vessel territory was involved in three patients, and three patients had involvement in double vessel territories. Regarding the summed stress score (SSS) value, most of the patients (four) had mild risk, whereas moderate and severe risk of a future cardiac event were observed in one patient each. In addition, two patients had left ventricular dysfunction (EF< 45%). Five patients with normal MPI and two patients with abnormal myocardial perfusion scans had high transient ischemic dilatation (TID). Risk factors such as male sex, hypertension, hyperlipidemia, obesity, and family history of CAD were not significantly correlated with abnormal scans. But abnormal scans were significantly related to a longer duration of diabetes (P = 0.038). Conclusion: This study showed that despite being asymptomatic, a considerable portion of diabetic patients had perfusion abnormalities, not just ischemia but also infarctions. Moreover, some of these patients are at high risk for future cardiac events as assessed by SSS, TID, and LVEF. Bangladesh J. Nuclear Med. 25(2): 110-116, 2022